TEACHERS’ LEVEL OF KNOWLEDGE, TRAINING AND COMPETENCY IN TEACHING AUTISTIC CHILDREN IN NASOM - Norsuhaily, Abu Bakar; Nurul Zulaikha, Raihan; Nurnadiah, Zamri (2020)
Autism is a developmental disorder that negatively impacts the ability for communication and interaction. Current statistics have reported an increase in its prevalence. Therefore, the need for well-trained NASOM teachers to teach children with autism has also increased. This study was implemented to investigate the level of knowledge, training and competency of autism’s teachers in NASOM. The location of the study chosen was on few branches of NASOM throughout in Malaysia. The research data were quantitatively obtained through the questionnaire. Questionnaire was distributed to 55 respondents consisting of men and women who teaches autistics in NASOM. Questionnaire forms have been divided into sections such as knowledge. However, they showed interest to undergo advanced courses to enhance their competence in educating children with autism. Thus, the ToT course and the module has to be improved by adding more components regarding autism. Teachers in NASOM also needed to be provided an access to the service of training in autism because the field of autism education has progressed and various strategies that have been proven effective scientifically are now available. Several suggestions by researcher have been proposed for improvement of studies of autistic students, training, competency and the presence to ToT course. The raw data obtained analyses using the SPSS version 20 software was analyzed again using t-test, correlation and regression. The findings shown that there was a difference to their knowledge, training and competency with their presence to ToT course. The ToT course was found to be rather ineffective as they have a moderate and low competency in teaching autistic students.